The retreat of western liberalism - Luce, Edward (New York Atlantic Monthly Press, 2017)
In The Retreat of Western Liberalism, Luce makes a larger statement about the weakening of western hegemony and the crisis of liberal democracy―of which Donald Trump and his European counterparts are not the cause, but a terrifying symptom. Luce argues that we are on a menacing trajectory brought about by ignorance of what it took to build the West, arrogance towards society's economic losers, and complacency about our system's durability―attitudes that have been emerging since the fall of the Berlin Wall. We cannot move forward without a clear diagnosis of what has gone wrong. Unless the West can rekindle an economy that produces gains for the majority of its people, its political liberties may be doomed. The West's faith in history teaches us to take democracy for granted. Reality tells us something troublingly different.
Includes bibliographical references.
Keywords: Liberalism